Temporal and Spatial Pattern of Expressway Construction in China from 1999 to 2019 and Its Correlation with Regional Economic Growth - Jialing Liang; Huiming Zong (Land)
As one of the important factors affecting regional economic development, expressway construction has been a concern of scholars worldwide. China’s highway construction is relatively late compared with Western developed countries, but the speed is faster. The construction is in step with China’s high-speed economic growth stage. However, there is temporal and spatial heterogeneity in expressway construction and economic development across different regions of the world, which has not been fully documented in the current literature. Using panel data from 1999 to 2019 encompassing expressway construction and regional economic development indicators of 233 prefecture-level cities in China, this paper delves into the dynamics of expressway infrastructure development and its correlation with regional economic growth. Using regression analysis, the study provides the following key insights: (1) As of 2019, expressway density exhibits a spatial pattern characterized by a higher density in major urban clusters and provincial capitals and a lower density in northeastern China and border regions. Between 1999 and 2009, the eastern region witnessed the fastest increase in expressway density, while the central region surpassed the eastern region in density growth during 2009–2019. Over the past two decades, there has been a significant overall increase in expressway growth nationwide, with the distribution of prefecture-level cities experiencing relatively faster growth rates aligning with the principles of the “National Highway Network Planning”. (2) Although there has been an overall increase in per capita GDP among prefecture-level cities, there has also been a widening disparity between these cities. Meanwhile, the total GDP of the central and western regions has experienced notable growth, effectively closing the gap with the eastern region. While total GDP demonstrates balanced development, per capita GDP displays a more varied pattern of growth. (3) Expressway density has played a positive role in fostering regional economic growth across the country over the long term. However, its impact has been more pronounced in the western region from 1999 to 2009 and increasingly significant in the eastern and central regions from 2009 to 2019.